Corruption Prevention In Village Fund Management - Harsya, Rabith Madah Khulaili (VJJ, 2020)
The potential for corruption in the management of village funds and for knowing efforts to prevent corruption in managing village funds. Management of village funds after the issuance of Law number 6 of 2014 concerning Villages experiences various kinds of problems between the emergence of criminal acts of corruption regulated in law number 20 of 2001 concerning Prevention of Corruption, so that the village government is expected to carry out various kinds of prevention against criminal acts of corruption both in terms of policy making, budget allocation and in the mechanism of policy making. Prevention of criminal acts of corruption must continue to be carried out starting from the lowest level, namely the village government so that in the future there will be realized a lawful village community that will increase the structure of good governance. Corruption prevention in managing village funds is trying to identify various modes of corruption in the village, increasing the capacity building of village officials and strengthening the capacity of village facilitators.